2021
DOI: 10.1111/1753-6405.13169
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand Youth19 survey: vaping has wider appeal than smoking in secondary school students, and most use nicotine‐containing e‐cigarettes

Abstract: Objective: To investigate smoking and vaping in secondary school students (aged 13-18 years) in New Zealand (NZ) following the introduction of 'pod' e-cigarettes, which have been associated with the rapid escalation of youth vaping elsewhere.Methods: Data on smoking and vaping were collected in 2019 as part of a comprehensive youth health survey (N=7,721). Results:Vaping was 2-3 times more prevalent than smoking, with 10% of students vaping regularly (monthly or more often), and 6% weekly or more often, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…3,[20][21][22] This is not universal though, with smoking increasing among some youth population subgroups. 21 From 1 October 2021 Australians require a prescription to legally access nicotine containing e-cigarettes. 1 While prior to this, legislation at a state level regarding the sale and regulation of e-cigarettes varied somewhat, all prohibited sales to minors (under 18 years).…”
Section: Heris Et Almentioning
confidence: 99%
“…3,[20][21][22] This is not universal though, with smoking increasing among some youth population subgroups. 21 From 1 October 2021 Australians require a prescription to legally access nicotine containing e-cigarettes. 1 While prior to this, legislation at a state level regarding the sale and regulation of e-cigarettes varied somewhat, all prohibited sales to minors (under 18 years).…”
Section: Heris Et Almentioning
confidence: 99%
“…Although a previous study in Australia has shown that not wanting to drive while intoxicated is a reason for using on‐demand services, 16 there is also evidence that needing to drive is a reason for choosing not to drink or drinking less; 34 the harms associated with both driving while intoxicated and increased individual consumption need to be considered collectively. Furthermore, although the harm‐reduction potential of e‐cigarettes is recognised, there are also concerns around health protection, from the – as yet – unclear impacts of increased e‐cigarette use, 35 particularly given the relative ease of access for young people 36 and emerging evidence of increasing uptake of e‐cigarette use those who have never smoked cigarettes 37 . In conclusion, the net public health benefits or costs of on‐demand access requires more careful scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the harm-reduction potential of e-cigarettes is recognised, there are also concerns around health protection, from the -as yet -unclear impacts of increased e-cigarette use, 35 particularly given the relative ease of access for young people 36 and emerging evidence of increasing uptake of e-cigarette use those who have never smoked cigarettes. 37 In conclusion, the net public health benefits or costs of on-demand access requires more careful scrutiny. Future research evaluating the positive and negative public health impacts of these services would be of substantial benefit.…”
Section: Discussionmentioning
confidence: 99%
“…While the US government has announced plans to drastically cut nicotine in cigarettes, New Zealand will be the first country to actually do so. One issue not addressed by the New Zealand law is vaping, which has largely replaced smoking among school age New Zealanders 2…”
Section: Current Adult Smokersmentioning
confidence: 99%